Transletramentos, saberes locais e era digital numa abordagem decolonial: tons, sentidos e perspectivas - Glasser, Adriane Elisa (2022)
In contemporary society, Digital Information and Communication Technologies (DICTs) have taken a central position in the social practices of subjects, visibly transforming social relations. However, although these DICTs are present in practically all social spheres, at school it is still seen with some fear and, sometimes, ends up generating some conflicts. With that in mind, the theme chosen for this thesis was the relationship between transliterations, local knowledge and the digital age, in a context of learning Portuguese, in a decolonial approach. Thus, the objective of this study was to develop a critical-collaborative, qualitative and interpretive action-research, of an ethnographic nature, from a perspective of transliterations, in Portuguese Language classes, with students from the 3rd grade of High School, from Colégio Estadual Ayrton Senna da Silva, in Foz do Iguaçu, seeking to develop contextualized practices that would contribute to a citizen, critical and expanded formation of the teacher and students. To this end, the theoretical basis was the studies of Paulo Freire (2021a, 2021b), Rojo (2012, 2013, 2015, 2019), Thomas (2007), Walsh (2013), Moran (2015), Morin (2010), Kleiman (1998, 2006, 2008) among others. For the generation of records, a transliteration project was developed, involving decolonial pedagogical practices that valued local knowledge and in which students interacted through multisemiotic texts, developing a more critical and reflective look at reality itself. With this research it was possible to perceive that the teaching of Portuguese language focused on the local reality, considering the DICTs as part of this new social constitution, requires contextualized practices that involve texts made up of the most diverse semioses, allowing the student and the teacher to perceive themselves as unfinished subjects, in a constant process of identity (re)construction, having language as a central element for a citizen, critical and expanded education.